The Evolution of EU’s Neighbourhood policy Towards eastern Europe - Ezel Tabur, Canan (Marmara Üniversitesi Avrupa Birliği Enstitüsü, 2013)
This article analyses the EU’s evolving relations with its eastern neighbourhood since the early 2000s, focusing on the diverging geographical preferences among the member states vis-à-vis the neighbourhood. In the past decade, the eastern shift of the EU borders in 2004 and 2007 paved the way for a significant increase in the political and financial commitments of the EU to its eastern neighbours. An EU level debate was launched regarding the need to enhance security and stability in the eastern neighbourhood in view of the then forthcoming enlargement. In 2004, the European Neighbourhood Policy (ENP) was put forward as a new foreign policy tool that integrated EU policies towards its eastern and southern neighbourhood under a single framework. However, the launch of the Eastern Partnership policy in 2009 demonstrated that a consensus has been developed among the member states with respect to enhanced bilateral and multilateral cooperation with the region. The article also evaluates the success of the Eastern Partnership policy regarding transformation of the relations between the EU and its eastern neighbours.
Keywords: EU external relations, European Neighbourhood Policy, Eastern Partnership, Eastern Europe